Analysis of Bacterial Community Structure of Activated Sludge from Wastewater Treatment Plants in Winter - Xu, Shuang (Biomed Res Int, 2018)
Activated sludge bulking is easily caused in winter, resulting in adverse effects on effluent treatment and management of wastewater treatment plants. In this study, activated sludge samples were collected from different wastewater treatment plants in the northern Xinjiang Uygur Autonomous Region of China in winter. The bacterial community compositions and diversities of activated sludge were analyzed to identify the bacteria that cause bulking of activated sludge. The sequencing generated 30087–55170 effective reads representing 36 phyla, 293 families, and 579 genera in all samples. The dominant phyla present in all activated sludge were Proteobacteria (26.7–48.9%), Bacteroidetes (19.3–37.3%), Chloroflexi (2.9–17.1%), and Acidobacteria (1.5–13.8%). Fifty-five genera including unclassified_f_Comamonadaceae, norank_f_Saprospiraceae, Flavobacterium, norank_f_Hydrogenophilaceae, Dokdonella, Terrimonas, norank_f_Anaerolineaceae, Tetrasphaera, Simplicispira, norank_c_Ardenticatenia, and Nitrospira existed in all samples, accounting for 60.6–82.7% of total effective sequences in each sample. The relative abundances of Saprospiraceae, Flavobacterium, and Tetrasphaera with the respective averages of 12.0%, 8.3%, and 5.2% in bulking sludge samples were higher than those in normal samples. Filamentous Saprospiraceae, Flavobacterium, and Tetrasphaera multiplied were the main cause for the sludge bulking. Redundancy analysis (RDA) indicated that influent BOD(5), DO, water temperature, and influent ammonia had a distinct effect on bacterial community structures.